Polimorfisme Penanda RAPD untuk Analisis Keragaman Genetik Pinusmerkusii di Hutan PendidikanUnhas - Gusmiaty, Gusmiaty; Restu, Muh.; Asrianny, Asrianny; Larekeng, Siti Halimah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2016)
The aims of Genetic study of pinus identified stand in Unhas Experimental Forest is to analyses of genetic characteristics of stand, based on RAPD (Random Amplified Polymorphic DNA) marker. The study was conducted in Biotechnology and Tree Breeding Laboratory, Forestry Faculty, Hasanuddin University. The method are DNA isolation, Primers selection and RAPD analyses. DNA analyses of Pine with ten RAPD marker showed number of alel varietied and polymorphic. Coefficient of similarity in population have number of 0.15-0.73.Highest genetic distance is 0.9630 and lowest genetic distance is 0.2698. Number of genetic diversity of Pine in Experimental Forest Hasanuddin University is 0,489 and categorized highly.